INVESTIGATION OF BUILDING INFORMATION MODELING (BIM) IN SUSTAINABLE CONSTRUCTION PROJECTS - Albert, Idowu; Nathaniel, Obaju Biodun; Olonilebi, Patience (FUDMA Journal of Sciences, 2025)
Building Information Modelling (BIM) is a transformative tool that significantly enhances the efficiency and sustainability of construction projects. Despite its global recognition, the adoption in of BIM in Nigeria, especially in sustainable construction, remains limited. This study investigates the role of BIM in optimizing material use, reducing waste, and promoting sustainable practices in construction projects, using Lagos State as a case study. A quantitative research approach was employed, gathering data through questionnaires distributed to construction professionals. The collected data underwent statistical analysis utilizing measures such as mean, standard deviation, and Relative Importance Index (RII) to extract meaningful insights. The findings revealed that while BIM offers substantial benefits in material optimization and project management, various barriers hinder its widespread adoption, including high software costs and limited technical expertise. Training programs, government support, and improved stakeholder collaboration are specific recommendation to increase BIM integration in sustainable construction projects.